Pengaruh “Nota Probowinoto” Terhadap Perubahan Strategi Pekabaran Injil di Gereja-Gereja Kristen Jawa - Santosa Budi Harjono (JURNAL TEOLOGI GRACIA DEO, 2019)
Based on historical research, the emergence of the "Probowinoto Note" was mainly caused by political and economic factors, especially political factors that occurred around the 1950s. In those days, relations between the Indonesian government and the government of the Kingdom of the Netherlands experienced severe tension. Everywhere there was a rejection from the Indonesian side of the Dutch people. "Probowinoto Note" Reverend Basoeki Probowinoto delivered a new concept of cooperation in anticipation of when the Akkoord Regionaal really stopped. By using the descriptive method of history, it can be concluded that the effect of the "Probowinoto Note" on the change in the strategy of the Gospel Message in the GKJ is the use of Christian foundations or institutions established by the church as means for inter-denominational churches to ally, testify and serve the community, develop guidelines the implementation of the preaching gospel according to the conditions of the GKJ by involving lay people. Abstrak Berdasarkan pada penelitian sejarah munculnya “Nota Probowinoto” lebih banyak disebabkan oleh faktor politis dan ekonomis, terutama faktor politik yang terjadi di sekitar tahun 1950-an. Pada masa-masa itu, hubungan antara pemerintah Indonesia dan pemerintah Kerajaan Belanda mengalami ketegangan yang hebat. Di mana-mana terjadi penolakan dari pihak Indonesia atas orang-orang Belanda. “Nota Probowinoto” Pendeta Basoeki Probowinoto menyampaikan sebuah konsep kerja sama baru guna mengantisipasi apabila Regionaal Akkoord benar-benar berhenti. Dengan menggunakan metode deskriptif hisotris, maka dapat disimpulkan pengaruh “Nota Probowinoto” terhadap perubahan strategi Pekabaran Injil di GKJ adalah dipakainya yayasan atau lembaga-lembaga Kristen yang didirikan oleh gereja sebagai sarana bagi gereja-gereja lintas denominasi bersekutu, bersaksi dan melayani masyarakat, menyusun pedoman pelaksanaan pekabaran Injil yang disesuaikan dengan kondisi GKJ dengan melibatkan kaum awam.